<p>Math I practice question</p>

<p>If f(x)=x^3 + 1 and if f^-1 is the inverse function of f, what is f^-1(4)? The answer if 1.44, but how would you do this problem? Thanks</p>

<p>Math I practice question</p>

<p>If f(x)=x^3 + 1 and if f^-1 is the inverse function of f, what is f^-1(4)? The answer if 1.44, but how would you do this problem? Thanks</p>

<p>solve for x in terms of y and switch the two. Then just plug in.

you would get: cube root of (x-1) = y.</p>

<p>Don't really understand your explanation.</p>

<p>f(x)=x^3 + 1

y = x^3 + 1

y - 1 = x^3

Cube root of (y-1) = x

Switch x and y.

Cube root of (x-1) = y

Plug in.

Cube root of (4-1) = y

Cube root of 3 = y , which is 1.44</p>

<p>Perfect, thanks so much, totally understand it now. I learned this earlier this year but totally forgot all of the inverse function stuff.</p>